Analisis dari perbandingan lokus kontrol manajer Berdasarkan Gender dalam meningkatkan kinerja karyawan di bank-bank yang dimiliki oleh pemerintah kota Makassar - Megawaty, Megawaty; Baharuddin, Ceskakusumadewi (Patria Artha University, 2017)
Analysis of Comparison Locus of Control’s Managers Based on Gender in Improving Employee Performance at Government-Owned Banks in Makassar City.The purposes of this research are to analyze the difference of locus of control managers based on gender in improving employee performance at government-owned banks in Makassar city and also to know more in which dimension the difference of locus of control based on gender in improving employee performance.The method of analysis used in this research is quantitative descriptive approach with Paired Samples Test. Data processing is done with the help of SPSS version 21.The results of this research indicate that there is difference of locus of control between male and female managers at government-owned banks in Makassar. But the difference is not so great because both male and female managers have answers with a mean or a similar average. However, the difference is considered significant when viewed from the value of the overall significance of all research instruments, with a value of 0.032 (smaller than 0.05). The results also show that there is no difference in the locus of control dimension between male and female managers in government-owned banks in Makassar because both male and female managers share the internal locus of control, the control centre who believes that everything happens to them because of their control.